Blood flow distribution in embryonic common snapping turtles Chelydra serpentina (Reptilia; Chelonia) during acute hypoxia and alpha-adrenergic regulation - Sartori, Marina R. [UNESP]; Kohl, Zachary F.; Taylor, Edwin W. [UNESP]; Abe, Augusto S. [UNESP]; Crossley, Dane A. (Elsevier B.V., 2019)
Embryonic turtles have four distinct vascular beds that separately perfuse the developing embryo's body and the extra-embryonic yolk sac, amnion and chorioallantoic membrane (CAM). The mechanisms enabling differential regulation of blood flow through these separate beds, in order to meet the varying demands of the embryo during development, is of current interest. The present investigation followed the changes in blood flow distribution during an acute exposure to hypoxia and after alpha-adrenergic blockade. We monitored heart rate (f(H)), mean arterial pressure (P-m), and determined relative blood flow distribution (%(Q) over dot sys) using colored microspheres. At 70% and 90% of the incubation period hypoxia elicited a bradycardia without changing P-m while %(Q) over dot sys was altered only at 70%, increasing to the CAM and liver. Blockade of alpha-adrenergic responses with phentolamine did not change f(H) or P-m but increased %(Q) over dot sys to the shell. These results show the capacity of embryos to redistribute cardiac output during acute hypoxia, however a-adrenergic receptors seemed to play a relatively small role in embryonic cardiovascular regulation.
Keywords: Cardiovascular; Cardiac output; Reptiles; Microspheres